Religion in Cyberspace: Islamic Religious Education in Social Media - Kambali, Kambali; Muslikh, Muslikh; Hidayat, Abas; Abdurakhman, R Nur (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Technology can give students more knowledge but can reduce moral values and social behavior. This phenomenon is a challenge faced by Islamic educators. Islam is not against the current development of digital media but provides teachings to use digital media wisely, which pays attention to morals and character. This research aims to analyze the role of Islamic religious education in social media. This research method is qualitative through a phenomenological approach. The results of the research show that through digital technology, it is hoped that it can instill religious values, and educators will continue to develop Islamic religious learning through the Internet media. The process of interaction through social media needs to pay attention to good communication ethics. Providing Islamic Religious Education is essential to avoid the behavior of Gibah, Su'udzon, Tajasuss, Slander, and Sukhriyah to provide understanding so that cyberbullying does not occur. The vulnerability of provocations through social media is that Islamic Religious Education is urgently needed to control negative provocations through social media. This research contributes to providing knowledge of the importance of Islamic religious education in social media in cyberspace.